2009
DOI: 10.1016/j.pscychresns.2008.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Reduced gray matter volume in ventral prefrontal cortex but not amygdala in bipolar disorder: Significant effects of gender and trait anxiety

Abstract: Neuroimaging studies in bipolar disorder report gray matter volume (GMV) abnormalities in neural regions implicated in emotion regulation, including ventral/orbital medial prefrontal cortex (OMPFC) GMV decreases and, more inconsistently, amygdala GMV increases. We aimed to examine OMPFC and amygdala GMV in bipolar disorder, type 1 patients (BPI) versus healthy control participants (HC), and examine potential confounding effects of gender, clinical and illness history variables and psychotropic medication upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(110 citation statements)
references
References 57 publications
7
101
0
2
Order By: Relevance
“…However, there is still some disagreement over the data pertaining to the cerebrovascular changes found between various studies, because of the different age of the patients and the regions where these changes are found (Almeida et al 2009), (Haller et al 2011), (Rej et al 2014). Further research is needed to establish the relationship between bipolar disorder and AD, and to ascertain whether these changes are directly related to the cognitive deficits found in both conditions.…”
Section: Bipolar Disorder and Alzheimer's Diseasementioning
confidence: 99%
“…However, there is still some disagreement over the data pertaining to the cerebrovascular changes found between various studies, because of the different age of the patients and the regions where these changes are found (Almeida et al 2009), (Haller et al 2011), (Rej et al 2014). Further research is needed to establish the relationship between bipolar disorder and AD, and to ascertain whether these changes are directly related to the cognitive deficits found in both conditions.…”
Section: Bipolar Disorder and Alzheimer's Diseasementioning
confidence: 99%
“…Cerebral perfusion reduction in different regions that we found should be studied and compared with our different psychometrics findings, which is not the objective of this study. Alterations in the prefrontal cortex are consistently implicated in psychiatric disorders, where studies have reported decreased metabolism, morphological changes [22] and increased oxidative damage [23]. Prefrontal cortex has a high relative density of dopaminergic projections compared with other cortical regions [24], and dopamine is involved in the regulation of working memory by the prefrontal cortex [25], which is impaired in patients with schizophrenia [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have found no differences in the caudate of bipolar disorder patients [107][108][109][110][111][112][113] or decreased caudate volume [114]. Similarly, putamen enlargement was reported [112,115,116], but other studies found no differences in the putamen [105,107,113] or decreased volume [117]. Studies also showed reduced volume in the nucleus accumbens [118,119].…”
Section: Gray Matter Alterationsmentioning
confidence: 99%